2013
DOI: 10.1158/1538-7445.am2013-1526
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1526: Evaluation of the novel tumor suppressor gene, β-Defensin-1, in colorectal cancer cell line models.

Abstract: Background: Human defensins are antimicrobial linear peptides with broad anti-microbial activity, organized into two classes, α- and β-defensins. Human β-Defensin 1 (hBD-1) is encoded by the DEFB1 gene located on chromosome 8p23 and functions as an antimicrobial peptide involved in the innate immune response. It is most often expressed in epithelial cells, including those in the large intestines. Previous experiments have shown that hBD-1 exhibits tumor suppressor functions in urothelial and kidney cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies have also reported it to be an important marker for colorectal cancer. A study by Layton et al[ 29 ] presented at American Association of Cancer Research 104th Annual Meeting in 2013 reported that β-defensins 1 was expressed in colon tissue samples of normal subjects while this expression was lost in subjects with colorectal cancer. While another study by Melle et al[ 30 ], reported that α-defensins are expressed more in colonic epithelium of patients with colorectal cancer than in normal epithelium, establishing defensins potential role as a tumor markers[ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also reported it to be an important marker for colorectal cancer. A study by Layton et al[ 29 ] presented at American Association of Cancer Research 104th Annual Meeting in 2013 reported that β-defensins 1 was expressed in colon tissue samples of normal subjects while this expression was lost in subjects with colorectal cancer. While another study by Melle et al[ 30 ], reported that α-defensins are expressed more in colonic epithelium of patients with colorectal cancer than in normal epithelium, establishing defensins potential role as a tumor markers[ 30 ].…”
Section: Methodsmentioning
confidence: 99%